Light scattering on phonons in quasi-one-dimensional antiferromagnet CsFeCl₃·2H₂O induced by magnetic ordering - Kurnosov, V.S.; Pashkevich, Yu. G.; Peschanskii, A.V.; Fomin, V.I.; Yeremenko, A.V. (Физика низких температур, 2002)
The appearance of new phonon lines in the Raman spectrum of the quasi-one-dimensional antiferromagnet CsFeCl₃·2H₂O as a consequence of magnetic ordering with a change of the unit cell volume was detected experimentally. An analysis of the possible mechanisms that might lead to the observed spectral features is done. A new mechanism of inducing Raman scattering on phonons from the boundary of the paramagnetic Brillouin zone is hypothesized.